The Effectiveness of Local Plants from Lom and Sawang Ethnics as Antimalarial Medicine - Henny Helmi; Budi Afriyansyah; Wiwied Ekasari (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2016)
Native people or ethnic societies that live in endemic malaria islands such as in Bangka Island and Belitung Island have used many medicinal plants to cure malaria. Leaves of kesembung (Scaevola taccada (Gaertn Roxb), roots of kebentak (Wikstroemia androsaemofolia Decne), and roots of medang mencena (Dapniphyllum laurinum (Benth) are the examples. This research was aimed to investigate the present of some biochemical compound and evaluate the antimalarial activity of ethanol extract of the plants against Plasmodium falciparum 3D7 in vitro. The IC50 level was determined through visual observation under microscope over 5000 of giemsa-stained erythrocytes then analyzed by probit analysis. Results showed that kebentak root ethanol extract was effective to inhibit P. falciparum 3D7 with level 0.485 µg/mL. Furthermore, the IC50 level of kesembung leaves and medang root were 44.352 µg/mL and 1486.678 µg/mL respectively. Phytochemical test result showed that kebentak leaf ethanol crude extract contained triterpenoid, kesembung root contained phenol and tannins; moreover, medang root contained alkaloid, saponin, and triterpenoid.How to CiteHelmi, H., Afriyansyah, B. Ekasari, W. (2016). The Effectiveness of Local Plants from Lom and Sawang Ethnics as Antimalarial Medicine. Biosaintifika: Journal of Biology Biology Education, 8(2), 193-200.